A Territorialização das greves em Ourinhos/SP, (2003/2012) - Souza, Anderson Aparecido de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The purpose of the following thesis is analyse facts that influence in the dynamic of strikes territorialisation and manifestations in the political context in Ourinhos. Capable elements of geography was used to visualize social dimensions which take part of facts consolidation of contraposition. In the homogenization process that has being unleashed due to the capitalist system increases. From the global scale we can understand how the relation of domination and control develops, which materialization can be analysed in a local spatial scale. The productive restructuring followed by technology revolution and associated to labour market deregulation, enabled a large regress and exploitation of workers raise. The economic side of international relations which the main characteristic still concentrated in unequal relations is represented by uneven and combined development. This is concretized in the Brazilian underdevelopment as an element of embrittlement of union resistance and proletarian Contributing to this analysis chart of politics, cultural and society dimensions, associated to relations of domination, followed by significant changes and influenced by different historic capital moments. Leading all the transformation factors of human life, the increase of exploration in the world of work, which the union structure suffers severe modification directed to the reduction of your combativeness. Observed in different locations, where one of them is the western region of São Paulo, more specifically in the city of Ourinhos...

O presente trabalho de conclusão de curso tem por objetivo analisar os fatores que influenciam na dinâmica de territorialização das greves e manifestações de âmbito politico territorial na cidade de Ourinhos. Utilizando para isso elementos de analise geográfica capazes de visualizar as dimensões sociais que participam da consolidação de fatores de contraposição, ao processo de homogeneização desencadeado pela ampliação do sistema capitalista de produção. A partir da escala global podemos compreender como se desenvolve as relações de dominação e controle, cuja materialização pode ser observada numa escala espacial local, a reestruturação produtiva acompanhada pela revolução tecnológica e associada à desregulamentação do mercado de trabalho, possibilitou um grande retrocesso e aumento da exploração dos trabalhadores. O âmbito econômico de relações internacionais cuja principal característica concentra-se ainda hoje, em relações desiguais, representada pelo desenvolvimento desigual e combinado, concretiza-se no subdesenvolvimento do Brasil como elemento de fragilização da resistência sindical e proletária. Contribuindo para este quadro de analise as dimensões políticas e culturais da sociedade, imbricadas nas relações de dominação, perpassando por significativas transformações, influenciadas pelos diferentes momentos históricos do capital. Levando ao conjunto de fatores de transformação da vida humana, o aumento da exploração no mundo do trabalho, cuja estrutura sindical sofre severas modificações direcionadas a redução de sua combatividade. Observadas em diferentes localidades, onde uma delas é a região do oeste paulista, mais especificamente a cidade de Ourinhos...
Keywords: Greves e lockouts - Ourinhos (SP); Manifestações públicas; Trabalho